STRATEGI PENGEMBANGAN WISATA BUDAYA BERBASIS KEARIFAN LOKAL DI DESA BUDO KABUPATEN MINAHASA UTARA - Lewan, Yurike; Pearl L Wenas; Michael C.S Mangolo; Debby Sendow (UHN IGB Sugriwa Denpasar, 2025)
Local wisdom-based culture is one part of tourism that needs to be developed. Budo Village, Wori District, North Minahasa has a culture that is still held by the community. The purpose of this study is to determine the potential and strategy for developing local wisdom-based cultural potential. This study uses a qualitative approach to data collection techniques with literature studies, observations and structured interviews. Data analysis is based on SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats analysis) Based on the results of the study, local wisdom-based cultural tourism in Budo Village includes: Tulude traditional festival; Mutual cooperation life of Mapalus togetherness; Ginto handicrafts and Masamper and Pato-pato dance arts. The results of the SWOT analysis formulated a strategy for developing local wisdom-based Cultural Tourism in Budo Village. 1) Increasing the development of cultural attractions for tourist attractions. 2) Involving the community in cultural performances and performances in order to maintain and preserve local culture and wisdom and improve community welfare. 3) Building awareness of the younger generation to preserve, maintain, and protect cultural attractions, arts and crafts for the sustainability of local community wisdom. 4) Improving accommodation such as facilities for organizing cultural attraction facilities 5). Improving cultural promotion activities and local wisdom of Budo village. The main development strategy is the development of human resources in preserving culture and local wisdom